A Phase Error Compensation Method for High-Rise Targets in High-Resolution SAR Images - JiaDong Deng; Wei Yang; HongCheng Zeng; YaMin Wang; Jiayi Guo; Wei Xiong; Min Liu; Jie Chen; Wei Liu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
High-resolution images of urban areas generated by spaceborne synthetic aperture radar (SAR) have a wide range of applications. However, with the improvement in resolution, the slant range error caused by the height of buildings leads to high-order and complex phase errors during the imaging process, which in turn causes image defocusing. To address this issue, an optimization algorithm is proposed based on the conjugate gradient method to estimate and compensate for the phase error. It uses image entropy as the optimization objective function, which is applicable to segmented images, effectively solving the problem of variation of phase error at different heights. In addition, the algorithm improves the computational efficiency by introducing a restart strategy and a momentum term in the 1-D line search. Experimental results using both simulation and actual SAR data show that the proposed algorithm outperforms the existing methods in terms of both efficiency and focusing quality.